Effect of seed coating in a combination of biopolymer, fungicide, and biocontrol agents on the vigour and stem rot incidence of groundnut under in-vitro condition: Effect of seed coating in a combination of biopolymer, fungicide, and biocontrol agents on the vigour and stem rot incidence of groundnut under in-vitro condition - S VIJAYKUMAR; R D PRASAD; B RAJESWARI; K S V P CHANDRIKA (Journal of Oilseeds Research, 2023)
The experiment was conducted with a combination of effective fungicide, potential biocontrol agents and seed coat biopolymer (chitosan) with different concentrations and their combinations along with untreated seeds as control, were used for coating groundnut seeds. The pathogen was inoculated on each treated and untreated seeds and the maximum germination of 94.0 % was recorded in T5 treatment having double layer seed coat which showed higher vigour index I and II (3190 and 87.4) and minimum seedling mortality of 10.7 %. Whereas untreated seeds (T1 ) showed low germination of 64.0 %, vigour index I and II (1709 and 44.6) with maximum seedling mortality of 75.2 %.